2012
DOI: 10.2495/ut120021
|View full text |Cite
|
Sign up to set email alerts
|

Environmental assessment of different vehicle technologies and fuels

Abstract: In this paper, a comparative LCA of conventional and alternative vehicles is performed. Thanks to a modeling approach combining LCA methodology, vehicle homologation data and statistical tools, all the available vehicle types in a given fleet are included in a single LCA model. Statistical distributions are used to include the variations of the main parameters (weight, fuel consumption and emissions) of all the considered vehicles in the LCA model. When dealing with greenhouse effect, battery electric vehicles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…The lowest score was EV production which was likely due to reduced utilization of copper and sulphuric acid during smelting of mineral ores (aluminium, copper, zinc, lead, and iron) for the engines. This is consistent with results from Boureima et al (2012). This is not always the case nevertheless when compared to another related study by Hawkins et al (2013) which indicates higher AP of 10% compared to base model.…”
Section: Figure 2 Human Toxicity Potential Of Passenger Vehicle Prodsupporting
confidence: 91%
“…The lowest score was EV production which was likely due to reduced utilization of copper and sulphuric acid during smelting of mineral ores (aluminium, copper, zinc, lead, and iron) for the engines. This is consistent with results from Boureima et al (2012). This is not always the case nevertheless when compared to another related study by Hawkins et al (2013) which indicates higher AP of 10% compared to base model.…”
Section: Figure 2 Human Toxicity Potential Of Passenger Vehicle Prodsupporting
confidence: 91%
“…It is therefore essential to take into account the influence of all the vehicle parameters on the LCA results. This paper is an update and a thorough extension of the work first presented at the 2012 Urban Transport Conference [19].…”
Section: Introductionmentioning
confidence: 97%
“…A detailed literature survey showed that there are several studies dealing with environmental impacts and total cost of ownership of vehicles separately [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Throughout the literature, the results are expressed in different units and based on different assumptions.…”
Section: Introductionmentioning
confidence: 99%